2022
DOI: 10.7759/cureus.28613
|View full text |Cite
|
Sign up to set email alerts
|

Status Quo in Mechanical Plaque Control Then and Now: A Review

Abstract: There are various kinds of dental diseases, of which dental caries and disease of periodontal origin are the most common. A very strong connection has been proven between oral inflammation and general health of an individual. Dental Biofilm is the main cause for gingivitis and periodontitis. Dental plaque may also be referred to as microbial plaque that consists of highly organized structures of different microbiotas attached to the hard tooth structure, which may be bound by salivary glycoproteins. Plaque con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Plak gigi mungkin hilang atau berkurang setelah pembersihan mekanis, baik manual maupun elektrik. Menyikat gigi ada sebagai kontrol plak mekanis yang membersihkan, menghilangkan dan mencegah penumpukan plak dan endapan lunak (materi putih dan sisa makanan) pada permukaan gigi dan sekitar gingiva (D'Elia et al, 2023;Toshniwal, Reche, Bajaj, & Maloo, 2022).…”
Section: Pembahasanunclassified
“…Plak gigi mungkin hilang atau berkurang setelah pembersihan mekanis, baik manual maupun elektrik. Menyikat gigi ada sebagai kontrol plak mekanis yang membersihkan, menghilangkan dan mencegah penumpukan plak dan endapan lunak (materi putih dan sisa makanan) pada permukaan gigi dan sekitar gingiva (D'Elia et al, 2023;Toshniwal, Reche, Bajaj, & Maloo, 2022).…”
Section: Pembahasanunclassified
“…8 American dental association reported that ideal bristles should not be sharpedged or rough. 9,10 Similarly with these reports Levrini et al suggested that it should be preferred to use round ended bristles in order to avoid soft tissue trauma and abrasion of dental hard tissues. 11 Silverstone and Featherstone were created a scale in 1988 for defining the form of tooth brushes.…”
mentioning
confidence: 92%
“…The use of oral care products is a behavior that can prevent gingivitis and periodontal disease, potentially reducing oral health inequalities that arise from the treatment of oral diseases due to varying income levels [9]. The American Dental Association (ADA) reports that using dental floss may remove up to 80% of dental plaque and recommends its use at least once daily [10]. However, various factors contribute to the persistently low rates of dental floss use [11,12].…”
Section: Introductionmentioning
confidence: 99%